2000
DOI: 10.1034/j.1600-0447.2000.90067.x
|View full text |Cite
|
Sign up to set email alerts
|

Extrapyramidal symptoms and oestrogen

Abstract: On the basis of these findings, and receptor studies in animals, it was concluded that oestrogen has different effects on dopamine dynamics in the mesolimbic and mesostriatal pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Fur-thermore, the estrogen group needed significantly less adjunctive anticholinergic medication to treat extrapyramidal side effects caused by haloperidol treatment. This finding is in line with other studies suggesting that estrogen treatment can also reduce the severity of antipsychotic medication-induced extrapyramidal side effects ( [47]). …”
Section: Intervention Studiessupporting
confidence: 93%
“…Fur-thermore, the estrogen group needed significantly less adjunctive anticholinergic medication to treat extrapyramidal side effects caused by haloperidol treatment. This finding is in line with other studies suggesting that estrogen treatment can also reduce the severity of antipsychotic medication-induced extrapyramidal side effects ( [47]). …”
Section: Intervention Studiessupporting
confidence: 93%
“…This may be due to the disease itself or the treatment given. The decreased BMD can be attributed to drug-induced decreases in levels of estrogen (Thompson et al, 2000;Salokangas, 1995;Riecher-Rossler & Hafner, 1993) and testosterone (Baptiste et al, 1999); it can also be attributed to polydipsia and decreased calcium to smoking, and to increased activity of several interleukins as well as to hyperprolactinemia (Dickson and Glazer, 1999) and hypercortisolemia (Halbreich & Palter, 1996). Additionally, it is reported that certain neuroleptics induce increased urinary Ca excretion through suppression of active vitamin D3 formation and that chronic treatment with certain neuroleptics may induce abnormal bone mineralization (Higuchi et al, 1987).…”
Section: Discussionmentioning
confidence: 97%
“…Thompson et al [95]) found clearly fewer EPS in patients with higher oestrogen plasma levels. The current state of research suggests that oestrogen may protect against EPS and TD [87], but due to inconsistent results and lack of exact testing of all the relevant factors the effect cannot yet be regarded as established [96,97].…”
Section: Oestrogen and Eps In Antipsychotic Treatmentmentioning
confidence: 95%